A Literature Review on Determinant Factors Related to Midwifery Performance in Antenatal Care (ANC) Services in Health Centers - Ni Putu Arik Diantari (Jurnal Indonesia Sosial Teknologi, 2024)
The maternal mortality rate (MMR) is one of the indicators that shows how the quality of health services is. Based on the results of maternal and perinatal audits, in general, cases of death due to obstetrics can still be prevented if health service efforts are adjusted to standards. The ability of health service facilities to carry out early detection and readiness of health workers, especially midwives, is important in comprehensive and quality pregnancy, childbirth, and postpartum services through continuous midwifery services. ANC examination services are one of the four safe motherhood concepts carried out to reduce AKI and need to be carried out in an integrated manner to improve the quality of ANC services at Puskesmas. The low coverage of KIA services by health workers is linked to midwifery performance problems. Midwifery performance problems are greatly influenced by various factors. The purpose of this study is to further explore the determinant factors related to the performance of midwives in antenatal care (ANC) services in Puskesmas. The approach used in this study is a study of literature with data sources in the form of original articles published in national/international journals through electronic databases such as Google Scholar and Garuda. The results of the study show that the individual factors are significantly related, namely ability, experience, and age; psychological factors that are significantly related, namely attitude and motivation; significantly related organizational factors, namely leadership, remuneration, length of service, employee status, facilities, and workload. The results of this study can be used as input for health service provider institutions to improve the quality of midwives in providing antenatal care (ANC) services.